2016
DOI: 10.3390/ma9120982
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Calculation of Frictional and Bending Moments at the Head-Neck Interface of Hip Joint Implants during Different Physiological Activities

Abstract: This study predicts the frictional moments at the head-cup interface and frictional torques and bending moments acting on the head-neck interface of a modular total hip replacement across a range of activities of daily living. The predicted moment and torque profiles are based on the kinematics of four patients and the implant characteristics of a metal-on-metal implant. Depending on the body weight and type of activity, the moments and torques had significant variations in both magnitude and direction over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A 3D model of a 32-mm diameter CoCr head with a 12/14 CoCr neck (as per dimensions reported by Rehmer et al [12]) was first analyzed under normal walking load profiles [24,25] in order to determine the most critical plane of the taper junction in terms of two important fretting wear parameters of normal contact stress (contact pressure) and micro-motion. An elastic-plastic material model was used for CoCr (ISO 5832-12) with a Young's modulus of 210 GPa, Poisson's ratio of 0.30, yield stress of 910 GPa, ultimate tensile stress of 1350 GPa, and tensile elongation of 15%.…”
Section: Methodsmentioning
confidence: 99%
“…A 3D model of a 32-mm diameter CoCr head with a 12/14 CoCr neck (as per dimensions reported by Rehmer et al [12]) was first analyzed under normal walking load profiles [24,25] in order to determine the most critical plane of the taper junction in terms of two important fretting wear parameters of normal contact stress (contact pressure) and micro-motion. An elastic-plastic material model was used for CoCr (ISO 5832-12) with a Young's modulus of 210 GPa, Poisson's ratio of 0.30, yield stress of 910 GPa, ultimate tensile stress of 1350 GPa, and tensile elongation of 15%.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 1, the forces and moments in this model were applied to the neck while the external surface of the head sphere was fixed in all directions. For each activity, all the three force components [20] and three moment components produced by the head and cup frictional sliding [26] were applied to the head-neck junction (Figure 2). Micromotions and contact pressure are found as the most important mechanical parameters which can control fretting wear and thereby fretting corrosion [14,27].…”
Section: Methodsmentioning
confidence: 99%
“…Force (N) profiles[20] and moment (Nm) profiles[26] for: (a) Stair up, (b) Stair down, (c) Sit to stand, (d) Stand to sit, (e) One leg standing, and (f) Knee bending activity cycles.…”
mentioning
confidence: 99%
“…The assembly force (4 kN) and the load components of level gait were applied to the bottom face of the neck. The forces were obtained from Hip98 software [12] and the frictional moments were calculated from a previous study for a 32 mm metal-on-metal bearing couple [26], as shown in Figure 1a. The maximum magnitude of the frictional moments in this 32 mm metal-on-metal bearing (with a friction coefficient of 0.20) was found to be 3.68 Nm.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the previously available contact forces [12,24,25], head-cup frictional moments have recently become available for walking activity [26,27]. This provides 6 DoF load inputs including three force components and three moment components [26]. However, the contribution of the frictional moments to the stress field, relative displacements between the contacting surfaces and consequently fretting wear behaviour has not been reported yet.…”
Section: What Are the Contributions Of Gait Forces And Frictional Mommentioning
confidence: 99%